Strategi Pengembangan Kompetensi Guru dalam Meningkatkan Kualitas Pendidikan di Era Society 5.0 - Muh. Hardi HR; Bess Wahida; Rizqi Eka Nanda (Pusdikra Publishing, 2026)
Advances in educational technology have prompted educational institutions to adapt in order to optimize their role as agents of change, including conditioning teachers as subjects of education. The focus of this study is to analyze the strategies employed to develop the competencies of teachers in the era of Society 5.0. The research was conducted using a Systematic Literature Review (SLR) approach. Data collection techniques were carried out in stages: determining the main keywords of the research theme, establishing inclusion and exclusion criteria, literature search, grouping and synthesizing findings. Data analysis was performed using content analysis and qualitative descriptive analysis, including data reduction, data presentation, and conclusion drawing. The reliability and objectivity of the research results were ensured through the validity of credible scientific sources, consistency in the analysis process and stages, and cross-checking between literature sources. The results of the study show that there are several strategies for developing teacher competencies in the era of Society 5.0, namely: intensive digital literacy training, collaboration through professional teacher networks, integration of artificial intelligence (AI) ethics into the teacher development curriculum, development of problem-based critical thinking skills, evaluation of teacher competency mapping through digital portfolios, partnerships with universities, psychological support, integration of machine learning, development of multicultural competencies, and leadership through mentoring. This study emphasizes the need for synergy between teachers, the government, and educational institutions to conduct regular and continuous training in teacher competency development so that there is an improvement in the quality of education in the era of society 5.0.